Strategi Guru Ips Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Ips Kelas VIII Di MTS Ma’arif Nu Blitar - Chusnul Chotimah; Dita Hendriani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to identify strategies used by social studies teachers in increasing student learning motivation in social studies subjects at MTs Ma'arif NU Blitar. The research method used is qualitative, with data collection through observation, interview, and documentation. Data analysis is carried out qualitatively descriptively, describing the situation based on written and oral data from the respondent. The results showed that teachers at MTs Ma'arif NU Blitar applied various learning strategies and methods, including the use of smart TVs and question and answer games, to increase student motivation and involvement in the learning process. These findings indicate that the strategy is effective in improving student learning outcomes, motivation, and performance.